High power (>1 W) room-temperature (300 K) 980 nm continuous-wave AlGaAs/InGaAs/GaAs semiconductor lasers - Kosiel, Kamil; Muszalski, Jan; Szerling, Anna; Bugajski, Maciej (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
A technology of high power, continuous-wave (CW) semiconductor lasers has been elaborated. AlGaAs/InGaAs/GaAs heterostructures, grown by molecular beam epitaxy (MBE), were used to fabricate laser diodes. The active region of laser diode was formed as strained, 8 nm thick, quantum well (QW) InGaAs layer. The AlGaAs layers of graded composition and graded refractive index (GRIN) formed the waveguide. Lasers were processed into wide stripe (W = 100 μm) mesas and were mounted on copper submounts and Peltier thermoelements in the standard TO-3 transistor housing. For stabilization of laser output, a silicon photodiode was placed next to a laser chip in the same case. Typical threshold current densities were 150 A/cm2, and the quantum efficiencies were of the order of 0.8 W/A. Lasers may work in pulsed regime as well as in CW regime with guaranteed optical power of 1 W at 300 K. The record threshold current densities achieved for 700 μm cavity were as low as 130 A/cm2 and the characteristic temperature was T0 = 200 K.
Optica Applicata, Vol. 37, 2007, nr 4, s. 423-432
Keywords: optyka; high power semiconductor laser; graded refractive index separate confinement heterostructure (GRINSCH); threshold current; external efficiency; parameter T0; Auger recombination; spontaneous radiative recombination; nonradiative recombination